2017
DOI: 10.17509/invotec.v13i1.6262
|View full text |Cite
|
Sign up to set email alerts
|

Development of Competency Based Assessment Model on Job Performance in Family Welfare Education Apprenticeship

Abstract: The assessment tool to evaluate learner performance on the apprenticeship is variety. Therefore, we were need a standardized assessment tool. This study was attempt to develop a competency based assessment model on job performance in apprentice of the family welfare education. Problem solving was conducted using research and development approach, through stages of: (1) a study introduction, (2) a development model, and (3) a validation model. The research subjects are internal and external tutors, also a learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Assessment components in this research cover the preparatory stage, processes and results that suitable with the hotel standard operating procedures [9]. They said that the application of the assessment was covering a preparation, collecting, judging, deciding and moderation stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment components in this research cover the preparatory stage, processes and results that suitable with the hotel standard operating procedures [9]. They said that the application of the assessment was covering a preparation, collecting, judging, deciding and moderation stages.…”
Section: Resultsmentioning
confidence: 99%
“…The testing instrument of the practice is covering the preparation, process of working and result which adapted to standard assessment competencies [8]. Another research revealed that development of the assessment tool performance based competency on industrial practices consist the planning and execution of the practice in assessment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Design of competency-based assessment model on the job performance in housekeeping department apprenticeship was adapted from competency-based assessment on job performance in family welfare education apprenticeship [3]. The housekeeping department apprenticeship was developed in research and development, involving planning assessment, an assessment tools and the judgment on housekeeping expertise.…”
Section: Resultsmentioning
confidence: 99%
“…It is applied to vocational education and is directed for measuring and evaluating the learner performance. It measures the learner cognitive, affective and psychomotor abilities, both direct and indirect evidence [3]. It measures not only their learning's activities, but also their learning proof (score or value of the test) in accordance with the performance criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation